Nasofrontal Complex Variation Frontal Sinus Drainage System Increases Frontal Rhinosinusitis Incident - Abdul Qadar Punagi (The Indonesian Biomedical Journal, 2016)
BACKGROUND: This research was conducted to find out the relation of anatomy variation of nasofrontal complex on the frontal sinus drainage system with frontal rhinosinusitis incident. METHODS: This research was using cross-sectional design involving 75 patients with chronic rhinosinusitis. Coronal paranasal sinus CT scan with sagittal plane reformat was carried out to examine. The CT scan figures were analyzed from every side and there were 150 samples found as the result. Data was analyzed using chi square test. RESULTS: The research indicates that there is no significant relation between frontal cell types, agger nasi cell, chonca media bullosa with incident of frontal rhinosinusitis (p>0.05). Prevalence of superior attachment of uncinate process (UP), type 1 (UP superior attachment on lamina papiracea) was found on 43 sides (28.6%), type 6 (UP superior attachment to medial turbinate) was found in 29 sides (19.3%). Prevalence of frontal rhinosinusitis was found in 42 (28%) from 150 sides. Group 1 drainage (medial side drainage; drainage to meatus medius [type 1-3]) was found in 32 sides (76.2%) and group 2 drainage (lateral side drainage; drainage to infundibulum ethmoid [type 4-6]) was found in 10 sides (23.8%). CONCLUSION: There is significant relation between frontal rhinosinusitis incident with variation of frontal sinus drainage (p<0.05) and drainage on group 1 has significant existence statistically on frontal rhinosinusitis incident. KEYWORDS: frontal rhinosinusitis, anatomy variation, nasofrontal complex, frontal sinus drainage